A expansão da OCDE na América Latina: análise dos processos de acessão dos países da região - Pereira, Lucas (2025)
This dissertation analyzes the expansion of the Organisation for Economic Co-operation and Development (OECD) in Latin America, highlighting why certain countries have opted to join the institution and how they have internalized its governance guidelines. The research departs from the premise that OECD membership is not merely a technical-administrative improvement but rather reflects strategic foreign policy decisions shaped by systemic factors and, above all, by domestic coalitions. To this end, a theoretical-methodological approach based on two pillars is adopted: (i) understanding institutional overlapping in the regio n- that is, the overlap of mandates and agendas (OECD, IDB, PA, EU) - which reinforces the dissemination of market oriented reforms; and (ii) analyzing foreign policy processes, emphasizing the leading role of governments, economic ministries, business groups, and think tanks. The study focuses on the four Latin American member countries (Mexico, Chile, Colombia, and Costa Rica), noting that although each has unique historical and economic characteristics, there is a fundamental convergence: the desire to project themselves globally and attract foreign investment, for which the OECD functions as a “seal of quality” bestowing international legitimacy. The research finds that the organization’s expansion in the region is tied both to the pursuit of credibility vis à-vis North Atlantic powers and to the support of governments seeking greater economic openness and integration into global value chains. Accordingly, it identifies domestic dynamics in which the business community, economic ministries, and the media wield decisive influence, displacing the traditional role of ministries of foreign affairs. Methodologically, the dissertation draws on official documents, OECD reports, academic articles, and newspaper coverage to triangulate different perspectives. The findings indicate that OECD membership arises from a complex process of domestic bargaining and convergence, facilitated by the joint activities of international institutions aligned with the agenda of developed countries. The conclusion is that the OECD’s expansion in Latin America, far from being merely functional, entails political and economic choices that involve disputes, definitions of international positioning, and institutional rearrangements calibrated to the standards of the West